Subspecies and Distribution. B.a.acutorostrataLacépede,1804—NAtlanticOcean. B. a. scammoni Demére, 1986 — N Pacific Ocean. An unnamed form is found in the Southern Hemisphere. in Balaenopteridae - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
Subspecies and Distribution. B.a.acutorostrataLacépede,1804—NAtlanticOcean. B. a. scammoni Demére, 1986 — N Pacific Ocean. An unnamed form is found in the Southern Hemisphere. Published as part of Russell A. Mittermeier & Don E. Wilson, 2014, Handbook of the Mammals of the World – Volume 4 Sea Mammals, Barcelona :Lynx Edicions on pages 242-299, DOI: 10.5281/zenodo.6596011